1981
DOI: 10.1111/j.1532-5415.1981.tb01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Burns in Older Patients

Abstract: An increasing percentage of the burn victims admitted to the Western Pennsylvania Hospital and Burn Care Center are aged 65 or older. Among 108 such elderly patients admitted during the past six years, 68 died and 40 survived--a mortality rate of 63 percent. Those who died of burns (average age 76.4) had burns over 44.8 percent of the mean body surface, whereas the survivors (average age 73.5) had burns over a smaller area (16.7 percent). Survival also was related to the presence of significant heart and lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…[15][16][17][18] Just as infants go through developmental phases in mastering locomotion and full use of all senses, older people develop a slow, subtle deterioration of their capacities, which may impede their ability to function but does not incapacitate them. 19 Several reports [20][21][22] have shown that at least 25% of patients who survive burn injury are able to maintain an independent lifestyle. This study has demonstrated that aggressive burn care results in a 72% survival rate (n = 159) in the older population.…”
Section: Commentmentioning
confidence: 99%
“…[15][16][17][18] Just as infants go through developmental phases in mastering locomotion and full use of all senses, older people develop a slow, subtle deterioration of their capacities, which may impede their ability to function but does not incapacitate them. 19 Several reports [20][21][22] have shown that at least 25% of patients who survive burn injury are able to maintain an independent lifestyle. This study has demonstrated that aggressive burn care results in a 72% survival rate (n = 159) in the older population.…”
Section: Commentmentioning
confidence: 99%
“…Other characteristics of the lung that make it one of the most susceptible organs to damage following injury include its delicate architecture and the presence of numerous alveolar macrophages that can independently respond to systemic cytokines [17,18]. The reasons why the lungs of aged individuals are even more susceptible to damage following injury than those of younger individuals, however, are not completely understood [4,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of the animal models that explore the mechanisms of pulmonary inflammation after injury use young adult animals [31][32][33][34]. Although many have shown that pulmonary sequelae have a higher incidence in elderly burn patients and are more detrimental, few have investigated the cause [2,4,19]. The main objective of this study was to examine pathologic differences in the lungs of young and aged animals in a murine model of burn injury and to determine whether the neutrophil chemokines, MIP-2 and KC, play a role in this process.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Various authors have identified issues surrounding hot tap water scalds, and reported on intervention programs aimed at reducing the incidence and severity of these scalds. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] A crucial factor is the temperature of the water. Many researchers have suggested that this must be targeted in any serious attempt to reduce the incidence and severity of hot tap water scalds because it is more practical to modify than any other factor.…”
mentioning
confidence: 99%